2020
DOI: 10.1038/s41598-020-65581-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines During Cardiac Rehabilitation After Heart Surgery and Their Association to Postoperative Atrial Fibrillation

Abstract: Inflammation is associated with atrial fibrillation (AF), but little is known about the association of AF with the inflammatory serum cytokines after the acute postoperative phase. Thus, we aimed to explore how plasma cytokines concentrations modify during a 3-week cardiac rehabilitation after heart surgery, comparing patients who developed postoperative AF (POAF) and those with permanent AF with patients free from AF (NoAF group). We enrolled 100 consecutive patients and 40 healthy volunteers as a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…and circulating IL-18 levels positively correlates with AF development. [44] , [45] , [46] However, whether and how IL-18 causes AF requires further extensive investigation.…”
Section: Mechanisms Of Af In Covid-19 Patientsmentioning
confidence: 99%
“…and circulating IL-18 levels positively correlates with AF development. [44] , [45] , [46] However, whether and how IL-18 causes AF requires further extensive investigation.…”
Section: Mechanisms Of Af In Covid-19 Patientsmentioning
confidence: 99%
“…128 However, recent clinical research indicated that post-operative AF patients had lower plasma levels of ADAM17 compared with patients free from AF, suggesting a possible beneficial effect of ADAM17 against post-operative AF occurrence. 129 This seemingly contradictory result may be partly caused by other clinical factors. Whether the role of ADAM17 in atrial remodelling is protective or harmful should be further clarified.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…Cardiovascular remodelling is caused by the activation of metalloproteinases and the breakdown of extracellular matrix components by IL-18. In addition, it has been found that circulating levels of IL-18 are linked to the development of atrial fibrillation (12) . (3) Cytokine storm:…”
Section: Introductionmentioning
confidence: 99%